2009
DOI: 10.4049/jimmunol.0803578
|View full text |Cite
|
Sign up to set email alerts
|

NKG2D-Dependent IL-17 Production by Human T Cells in Response to an Intracellular Pathogen

Abstract: We studied the factors that control IL-17 production in human Mycobacterium tuberculosis infection. CD4+ cells from healthy tuberculin reactors produced IL-17 in response to autologous M. tuberculosis-stimulated monocytes, and most IL-17+ cells were Ag experienced, CD4+CD62L−. IL-17 production by CD4+ cells was inhibited by anti-IL-23, but not by Abs to IL-1, IL-6, or TGF-β. Anti-NKG2D reduced IL-17 production and the frequency of CD4+CD62− IL-17+ cells, suggesting that NKG2D stimulates IL-17 production. CD4+N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…This was further supported by the finding that M. tuberculosis products down-regulate IL-6R expression on CD4 1 T cells in vitro. However, this may be challenged by the report by Paidipally and colleagues (20), which indicated that, in individuals with M. tuberculosis infection, IL-6 is not required for T cells to produce IL-17 in response to mycobacterial antigens. Nevertheless, the expansion of antigen-experienced Th17 cells evaluated by Paidipally and colleagues is different from differentiation of Th17 subsets from naive T cells-a process in which IL-6R-mediated signaling is required.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This was further supported by the finding that M. tuberculosis products down-regulate IL-6R expression on CD4 1 T cells in vitro. However, this may be challenged by the report by Paidipally and colleagues (20), which indicated that, in individuals with M. tuberculosis infection, IL-6 is not required for T cells to produce IL-17 in response to mycobacterial antigens. Nevertheless, the expansion of antigen-experienced Th17 cells evaluated by Paidipally and colleagues is different from differentiation of Th17 subsets from naive T cells-a process in which IL-6R-mediated signaling is required.…”
Section: Discussionmentioning
confidence: 94%
“…Although other mechanisms, such as the inhibitory functions of Th1 and Th2 cytokines, as well as nature killer group 2D (NKG2D) expressed on CD4 1 T cells, may be involved in regulating Th17 responses in M. tuberculosis infection, these are mostly related to regulation of the differentiated antigenspecific, but not nonspecific, Th17 responses (20,21,35,36). Our finding, that down-regulation of IL-6R expression on CD4 1 T cells in patients with active TB diseases, suggests that it may be an important mechanism driving the suppressed, nonspecific Th17 responses in patients with TB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase of mycobacterial Ag-specific IL-17A production was reported in peripheral blood of healthy tuberculosis contacts (49) or tuberculin-positive individuals (50). Furthermore, an increase of IL-17A-producing TCR gd T cells was reported in peripheral blood of patients with tuberculosis (51).…”
Section: Discussionmentioning
confidence: 96%
“…Increasing studies have reported that Th17 cells are the main IL-17-producing cells and contribute to protective immunity against Mycobacterium tuberculosis (Khader et al, 2007;Chen et al, 2009;Paidipally et al, 2009). Khader et al (2007) reported that Th17 response had a role in protective immunity in M. tuberculosis infection, and M. tuberculosis infection was correlated with a decreased Th17 response because of suppressing Th1 cytokines (Khader et al, 2007).…”
Section: Introducionmentioning
confidence: 99%